Measurement theory and practice in kinesiology - Wood, Terry M. 1949-; Zhu, Weimo 1955- (Human Kinetics, 2006)
In this book, kinesiology is presented without the need to work through rigorous equation sets. Researchers and students can fathom the conceptual basis for topical measurement techniques and their application, and they are exposed to measurement issues in various physical activity fields. The text grounds readers in measurement basics in an easy-to-understand fashion and is for non-measurement specialists who deal with measurement in various physical activity fields. It takes full advantage of the advances in computer technology and programming to offer an array of advanced test construction and modeling methodologies to researchers and practitioners. And it describes new methods in handling both large and small data sets. The book provides a contemporary reference on measurement issues